PENINGKATAN PENGETAHUAN SISWA SD TENTANG MANFAAT BUAH DAN SAYUR DENGAN MENGGUNAKAN MEDIA LEAFLET - Anggun Khairunnisa; Manjilala; Agustian Ipa; Adriyani Adam (Media Gizi Pangan, 2023)
Children in Indonesia have a habit of consuming very low fruits and vegetables. Result of Riskesdas in 2018 shows that overall the population of age > 5 years lacked 95,5% of the fruit and vegetables. The aim of this research is to determine the effect of Leaflet media education on increasing knowledge about the benefits of consuming fruit and vegetables in primary school children. This study was a Pre-Experimental Design With One Group Pretest-Posttest Design Carried Out at the Inpres Sudiang Makassar. The samle size in this study was 97 people taken by the total sampling. Variables in the study were knowledge of primary school student before being given an intervention in the form of education through leaflet media and knowledge after intervention. The effect of variables using questionnaires was tested by using the wilcoxon test. The results showed that in SD Inpres Sudiang Makassar, the age was generally 60.8%, the class was generally 27.8%, and the gender was generally 25.8%. The father's occupation was generally private employee (29.9%), while the mother's occupation was generally a housewife (77.3%). The level of knowledge before education was generally good (85.6%), while the level of knowledge after education was generally good (100%). Statistical analysis showed a difference in nutritional knowledge before and after the provision of media leaflet education (p = 0.000). It is recommended for further research, it is expected to be able to develop educational media in accordance with the development of technology so thah it supports interest and reading interest and reading interesr for respondents.